2018
DOI: 10.1016/j.jvs.2017.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes and evolution of gutter area after endovascular aneurysm repair with the chimney graft procedure

Abstract: Midterm results show that a standardized procedure for EVAR using chimney grafts for branch vessel preservation is an acceptable option for high-risk patients with large, complex aneurysms who are unfit for open repair and who have been excluded from fenestrated EVAR. Gutter size decreases over time, but the rate of branch vessel loss and reinterventions demonstrate that this approach should remain reserved for those who are at truly prohibitive risk for open or fenestrated stent graft repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
1
8
0
1
Order By: Relevance
“…In terms of technique, the approach utilized suffers from the limitation that chimney graft would possibly enlarge the risk of endoleak. [16,17] Therefore, the present findings confirmed that the PAU was located at the anterior wall of aorta arch, so that the graft we chose was oversized, nearly 10% to 15% larger than the precise diameter of aorta and the chimney stent was implanted at the posterior wall of graft in order to decrease the risk of endoleak.…”
Section: Discussionsupporting
confidence: 73%
“…In terms of technique, the approach utilized suffers from the limitation that chimney graft would possibly enlarge the risk of endoleak. [16,17] Therefore, the present findings confirmed that the PAU was located at the anterior wall of aorta arch, so that the graft we chose was oversized, nearly 10% to 15% larger than the precise diameter of aorta and the chimney stent was implanted at the posterior wall of graft in order to decrease the risk of endoleak.…”
Section: Discussionsupporting
confidence: 73%
“…8 Small paragraft gutters do not influence successful endovascular repair, since they are occluded by progressive thrombus formation during early follow-up. 5,25 In addition, de Beaufort et al 31 describe a reduction of gutter sizes in CG configurations during follow-up. Hence, most perioperative type Ia endoleaks do not persist during midterm follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, most perioperative type Ia endoleaks do not persist during midterm follow-up. 5,8,25,31 However, Niepoth et al 17 state that these paragraft gutters might increase or decrease based on vascular wall movements and through the force of blood pressure on the proximal sealing zone, which could lead to aneurysm growth and the need for secondary interventions. It should be noted, though, that the geometrical changes in paragraft gutters observed in our static models in a gelatin-water environment were not tested for the influence of pressure or spontaneous thrombosis of these gutters.…”
Section: Discussionmentioning
confidence: 99%
“…The main source of these leaks is the gutter that arises from inadequate sealing between the parallel grafts. [18][19][20] Such gutters are difficult to seal completely with the current techniques 20 ; however, longer overlapping of chimney grafts with the main graft may reduce the gutter size. 3 The fenestration technique, on the other hand, can result in complete sealing of the main graft and branches to the aortic wall and arteries, respectively.…”
Section: Discussionmentioning
confidence: 99%